Bridging Political Divides: Perceived Threat and Uncertainty Avoidance Help Explain the Relationship Between Political Ideology and Immigrant Attitudes Within Diverse Intergroup Contexts - Stewart, Brandon D.; Gulzaib, Fyqa; Morris, David S. M. (Frontiers in Psychology, 2019)
The political divide between liberals and conservatives has become quite large and stable, and there appear to be many reasons for disagreements on a wide range of issues. The current research sought to explain these divides and to extend the Uncertainty-Threat Model to intergroup relations, which predicts that more dispositional, perceived-threat and more uncertainty-avoidance will be related to more political conservatism. Given that conservatism is also often related to more negativity to low-status groups such as immigrants, the relationship between political ideology and negative attitudes toward immigrants may be mediated by more threat and uncertainty-avoidance. Study 1 tested this mediational hypothesis in a correlational design and showed that both uncertainty-avoidance and perceived realistic and symbolic threat significantly mediated the relationship between political ideology and attitudes toward immigrants, and that perceived threat was the more influential mediator. Study 2 extended threat management to perceived threats from unspecified outgroups, as opposed to the immigrant outgroup, and it replicated all significant mediations. Study 3 replicated the Study 1 and Study 2 mediations of political ideology to attitudes toward immigrants with uncertainty-avoidance and perceived threat from immigrants as mediators; it further replicated the mediations to the negative attitudes measure that had been used in Study 2 and it extended it to an objective and indirect bias measure (i.e., Affect Misattribution Procedure). Overall, almost all of the results supported the idea that perceived threat and uncertainty-avoidance both mediate the relationship between political ideology and attitudes toward immigrants, and that threat management, as opposed to negativity bias, may be a central concern separating liberals and conservatives. Within all three studies, we also observed more evidence for the Uncertainty-Threat Model predictions than we did for the alternative Extremity Hypothesis, which predicted a quadratic relationship between political ideology and threat and uncertainty, and between political ideology and attitudes toward immigrants.